2022
DOI: 10.3389/fphar.2022.837671
|View full text |Cite
|
Sign up to set email alerts
|

The Kappa Opioid Receptor: A Promising Therapeutic Target for Multiple Pathologies

Abstract: Kappa-opioid receptors (KOR) are widely expressed throughout the central nervous system, where they modulate a range of physiological processes depending on their location, including stress, mood, reward, pain, inflammation, and remyelination. However, clinical use of KOR agonists is limited by adverse effects such as dysphoria, aversion, and sedation. Within the drug-development field KOR agonists have been extensively investigated for the treatment of many centrally mediated nociceptive disorders including p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 272 publications
(268 reference statements)
1
31
0
1
Order By: Relevance
“…38 The kappa-opioid (KOP) receptor is an opioid receptor that has implications in analgesia, stress, depression, sedation, and diuresis. 39 In a study involving mice, KOP receptor antagonism caused increase seizure-like activity while receptor agonism caused a reduction in seizure-like activity. 40 In addition, inhibition of the serotonin and norepinephrine reuptake pathway has been postulated as a mechanism behind tramadol's adverse effect of lowering the seizure threshold.…”
Section: Oud and Seizure Among Patients With Audmentioning
confidence: 99%
“…38 The kappa-opioid (KOP) receptor is an opioid receptor that has implications in analgesia, stress, depression, sedation, and diuresis. 39 In a study involving mice, KOP receptor antagonism caused increase seizure-like activity while receptor agonism caused a reduction in seizure-like activity. 40 In addition, inhibition of the serotonin and norepinephrine reuptake pathway has been postulated as a mechanism behind tramadol's adverse effect of lowering the seizure threshold.…”
Section: Oud and Seizure Among Patients With Audmentioning
confidence: 99%
“…The address region containing multiple basic amino acid residues was suggested to be responsible for the KOR efficacy. Although the relatively large size of the molecule and the extensive metabolism are more problematic, many studies demonstrated important roles of DYN A and its target receptor, KOR, in pain and other disorders such as depression, anxiety, and drug abuse, and more interest is being focused on the therapeutic potentials of KOR agonists and antagonists [ 182 , 183 , 184 ].…”
Section: Peptidomimetics For Opioid Receptorsmentioning
confidence: 99%
“…The wide expression of the κ-opioid receptor (KOR) throughout the central nervous system (CNS) and the peripheral nervous system (PNS) and its involvement in the control of important physiological processes including antinociception, motivation, emotion, and cognition have stimulated the development of KOR ligands for the treatment of pain, itch, and neuropsychiatric disorders. , KOR agonists provide promising potential to develop safer and more effective analgesics since they lack the undesired effects typical for μ- (MOR) and δ- (DOR) opioid receptor agonists, including respiratory depression, constipation, tolerance, or addiction . Nevertheless, opioid-mediated activation of KOR is often associated with sedation, dysphoria, and hallucinations, which have precluded the clinical development of KOR agonists. , Over recent years, biased opioid ligands selectively activating the G protein over β-arrestin signaling pathways have provided an avenue to develop therapeutics with reduced KOR side effects .…”
Section: Introductionmentioning
confidence: 99%